The isolated posterior malleolar fracture and syndesmotic instability: A case report and review of the literature. (2017) - Smeeing, Diederik P.J.; Houwert, Roderick M.; Kruyt, Moyo C.; Hietbrink, Falco
Highlights: An isolated fracture of the posterior malleolus can be a sign of a more complex injury. A posterior malleolar fracture can be associated with other ligamentous and syndesmotic injuries or other lower leg fractures. An isolated posterior malleolar fracture can easily be missed on plain radiographs. Diagnostic work-up of an isolated posterior malleolar fracture includes a CT-scan. If diagnosed and treated properly, it has a good long-term functional outcome. Abstract: Introduction: Ankle fractures are among the most common type of fractures in the lower extremity. A posterior malleolar fracture is frequently part of a more complex ankle fracture and only in rare cases it occurs as isolated injury. Posterior malleolar fractures often occur with associated injuries, such as a Maisonneuve fracture or with bi- or trimalleolar ligamentous injuries. Knowledge about these associated injuries is essential to prevent missed diagnoses. The aim of this article is to describe the isolated posterior malleolar fracture, the possible associated injuries, the diagnostic work-up and therapeutic consequences. Presentation of case: We present a case of a 26-year-old male patient who sustained an isolated posterior malleolar fracture with 4.5 years follow-up. Discussion: Isolated fractures of the posterior malleolus are uncommon injuries. Diagnosis, treatment and outcome can seldom be extracted from large series. However, several cases have been described in literature, which we have summarized. Conclusion: This case report and literature review shows that isolated posterior malleolar fractures might occur as part of a more complex ankle injury, in combination with a fracture of the lower leg or after high energy trauma. Physicians should be aware of these associated injuries. Diagnostic work-up should include X-rays of the knee and lower leg and a CT scan of the ankle. If diagnosed and treated properly, isolated posterior malleolar fractures have a good long-term functional outcome.